Results of 1‑year follow‑up after umbilical hernia with rectus abdominis muscle diastasis repair using endoscopic subcutaneous onlay approach (SCOLA) - Mindaugas Kiudelis; Matas Pažusis; Linas Venclauskas; Eglė Kubiliūtė; Algirda Venclauskienė (Videosurgery and Other Miniinvasive Techniques)
Introduction: Endoscopic subcutaneous onlay approach (SCOLA) mesh repair in combination with anterior plication of diastasis has recently become a commonly performed procedure.